Synthesis and Biological Evaluation of 3-(Pyridine-3-yl)-2-Oxazolidinone Derivatives as Antibacterial Agents - Jin, Bo; Wang, Tong; Chen, Jia-yi; Liu, Xiao-qing; Zhang, Yi-xin; Zhang, Xiu-ying; Sheng, Zun-lai; Yang, Hong-Liang (Frontiers in Chemistry, 2022)
In this research, a series of 3-(pyridine-3-yl)-2-oxazolidinone derivatives was designed, synthesized, and evaluated for in vitro antibacterial activity, which included bacteriostatic, morphological, kinetic studies, and molecular docking. The results demonstrated that compounds 21b, 21d, 21e and 21f exhibited strong antibacterial activity similar to that of linezolid toward five gram-positive bacteria. After observing the effect of the drug on the morphology and growth dynamics of the bacteria, the possible modes of action were predicted by molecular docking. Furthermore, the antibiofilm activity and the potential drug resistance assay was proceeded. These compounds exhibited universal antibiofilm activity and compound 21d showed significant concentration-dependent inhibition of biofilm formation. Compound 21d also showed a stable effect on S. pneumoniae (ATCC 49619) with less drug resistance growth for 15 days, which is much longer than that of linezolid. Overall, these results can be used to guide further exploration of novel antimicrobial agents.